Colorectal cancer prevention in the Czech Republic: time trends in performance indicators and current situation after 10 years of screening - Suchanek, Stepan; Majek, Ondrej; Vojtechova, Gabriela; Minarikova, Petra; Rotnaglova, Barbora; Seifert, Bohumil; Minarik, Marek; Kozeny, Pavel; Dusek, Ladislav; Zavoral, Miroslav (European journal of cancer prevention, 2014)
The incidence and mortality of colorectal cancer (CRC) in the Czech Republic is significant. The National CRC Screening Program started in 2000 and was further enhanced in 2009. In 2010, the European Guidelines were introduced. The aim of the present trend study was to evaluate the quality of the Czech National Colorectal Cancer Screening Program using early performance and long-term impact indicators. The screening program has been assessed using data from three sources: the Czech National Cancer Registry, the Czech National Reference Centre, and the Czech CRC Screening Registry. The data were compared with a set of recommended quality control indicators. Between 2006 and 2010, a total of 1 881 299 fecal occult blood tests were performed, of which 87 397 were positive (4.6%). Until 2011, a total of 68 527 fecal occult blood test follow-up colonoscopies were performed. In addition, between 2009 and 2011, a total of 10 309 screening colonoscopies were performed. As a result, a total of 25 255 adenomas (32.0% rate) and 3379 CRCs (4.3% rate) were detected. A trend of cancer detection in earlier stages has been observed. The overall program coverage has increased to 22.7% of the target population in 2010. The majority of European guidelines' quality indicators for nonpopulation-based programs were implemented in the Czech National CRC Screening program. An improvement in program management was accompanied by an increase in coverage as well as other performance indicators.
Keywords: ukazatele kvality zdravotní péče; kolonoskopie; Male; kolorektální nádory; Survival Rate; následné studie; prognóza; Česká republika; Neoplasm Staging; mužské pohlaví; Colonoscopy; míra přežití; Follow-Up Studies; Czech Republic; Time Factors; lidé; ženské pohlaví; Quality Indicators, Health Care; Humans; Early Detection of Cancer; časové faktory; Colorectal Neoplasms; Prognosis; Female; lidé středního věku; staging nádorů; časná detekce nádoru; Middle Aged